Osteomorphometrical Characterization of Thigh, Leg and Pes Region of Sahiwal Cattle - Chaurasia, D. (Indian Journal of Veterinary Anatomy, 2020)
The gross osteomorphometrical study was conducted on skeleton of eleven adult Sahiwal cattle irrespective of sex. Circumference of shaft of femur was maximum in distal third. Trochanteric fossa was divided into large shallow and small deep parts. The medial angle of patella was approximately thirty degree greater than lateralangle. In the posterior surface of tibia five linea muscularis were observed. The approximate ratio between length and width of sustentaculum tali was 2:1. Dorsal longitudinal groove was deepest and widest in distal part of metatarsal bone. It can be concluded that these characteristic osteometric data will be certainly one of theimportant tool for breed identification in forensic study.